Introduction to managerial economics - Cassimatis, Peter J. (London : Routledge, 1996)
Economic model of the firm. Profitability analysis. Long-range planning. Decision and risk analysis. Economic environment.
Keywords: Economics; Managerial economics; Managerial economics